Сurrent state and prospects for application of a high power electron beam technology to produce metallic and nonmetalic components for electric contacts and electrodes - Grechanyuk, N.I.; Minakova, R.V.; Grechanyuk, I.N.; Miedzinsk, i B.; Xu, L.J. (Электрические контакты и электроды, 2014)
In the paper current state and prospects of applicability of a high power electron beam technology for manufacturing both metallic and nonmetallic composite materials mostly for electric contacts and electrodes are presented and discussed.